Correlation of Cardiorespiratory Fitness Levels with Functional Mobility Abilitiy in Post Thrombotic Infarction Stroke Patient - Eny Susilowati1, Reni Hendrarati Kusharyaningsih2, Dewi Poerwandari2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Stroke patients often experience functional ambulation difficulties and lack ability to walk independently due to the reduction cardiorespiratory fitness so that an understanding of the relationship between fitness levels cardiorespiratory with functional mobility ability is needed, especially for thrombotic infarction stroke patients.. Objectives: This study aims to assess the relationship between cardiorespiratory fitness levels with functional mobility ability in the first three months after thrombotic infarction stroke. Method: Subjects are 38 post trombotic infarction stroke. Functional mobility is measured by the Timed Up and Go test. Subjects were asked to stand up from a chair whose seat is ± 46cm and the height of its back is 65cm, walk as far as 3 m, turn 1800, walk back and sit back. Data were analyzed and performed statistical test using SPSS 17. Results: The study showed the average TUG test was 15.56-7.79 seconds with the longest travel time was 37.38 seconds and the fastest travel time was 8.16 seconds. The average of VO2max was 10.62 ± 2.31mL / kg / min, with the lowest VO2max yield of 5.78mL / kg / min and the highest was 14.54mL / kg / minute. The TUG test had a negative correlation with VO2max the 6 minute walk test result. Conclusion: There is a significant relationship between cardiorespiratory fitness level and functional mobility abilities in post thrombotic infarction stroke patient